THE IMPACT OF DIGITAL TOOLS ON ENGLISH LANGUAGE LEARNING (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the impact of digital tools on English language learning and their role in improving students’ language skills. The rapid development of information and communication technologies has significantly influenced educational systems worldwide. Digital tools such as mobile applications, online platforms, virtual classrooms, multimedia resources, and interactive software have created new opportunities for effective language learning.The results of the research show that digital tools positively influence English language learning by improving accessibility, interactivity, and personalization of education. The findings suggest that the integration of digital tools enhances learning outcomes and prepares students for modern communication environments.
Keywords: digital tools, English language learning, technology in education, online learning, language skills, ICT, e-learning.